Variation of crystal lattice parameters of KDP single crystals containing impurities - Salo, V.I.; Tkachenko, V.F. (Functional Materials, 2008)
KDP single crystals grown from aqueous solutions by the recirculation method from nominally "pure" raw material and added impurities Ca, Si, Pb, Cr, hydrogen peroxide were studied by high resolution X-ray method. It was found that additional introduction of impurities leads to a deterioration of structural quality of crystals. The main growth defects of crystals at dislocation density ~ 10² cm⁻² at the absence of zonarity and sectoriality is the impurity striation and presence of low-angle quasi-boundaries. A correlation between the concentration of low-angle quasi-boundaries, dispersion of structure-sensitive parameters and the bulk laser damage resistance of crystals is observed.